Digital food from paddock to platform - Lewis, Tania (Contemporary food studies, 2020)
"Tania Lewis offers the first critical account of the impact of digital information, media, and communication technologies on the topic of food. Lewis critically analyzes how our relationship to food consumption, production, and politics is being re-mediated through digitally connected electronic devices, practices and content. By drawing together the world of food and the digital, the book speaks to a number of pressing contemporary themes including the tensions around digital engagement in increasingly commercialized spaces; the changing nature of politics in a social media context; the growing naturalization of digital devices and related practices of data monitoring; and the role and impact of digitization on social relations. At the forefront of critical new research, and written with a student readership in mind, this text is essential for scholars interested in media studies, cultural studies, food studies, and cultural geography."--